Partial cross sections of 181Ta(n, γ) using BEGe detectors. (October 2020) - Heftrich, T.; Weigand, M.; Brückner, B.; El Mard, A.; Göbel, K.; Khasawneh, K.; Kisselbach, T.; Kurtulgil, D.; Reich, M.; Reifarth, R.; Sheriff, S.; Volknandt, M.
Abstract: Heavy nuclei are mainly synthesised by a sequence of neutron captures and β -decays. The corresponding neutron energies in the different astrophysical sites range from 1keV to 1MeV. By using the activation technique, small neutron capture cross sections can be studied. A sample is irradiated by a quasi-stellar neutron spectrum in order to produce radioactive isotopes. The decay of the radioactive nuclei can be detected by their characteristic gamma rays. For this purpose, sensitive experimental detector equipment is needed. Two Broad Energy Germanium Detectors (BEGe) were recently built up at the Goethe University Frankfurt. The first measurement of the partial neutron capture cross sections for the reaction 181 Ta(n, γ ) has been performed by using the activation technique.